Identification And Classification of Tattoos In Autopsies; A Retrospective Study - Hatice Kübra Ata Öztürk; Kemalettin Acar; Ayse Kurtuluş Dereli (Gazi Medical Journal, 2025)
Objective: Figures created under the skin using Indian ink or carbon are called tattoos. Each figure has different meanings, such as freedom and sexuality. In forensic medicine, tattoos are used for human identification. Tattoos can help determine the origin of death by providing information about individuals' lifestyles. Our study aims to analyze the profile of tattoos, define and classify tattoos, and emphasize their importance in forensic medicine. Additionally, we aimed to reveal whether there was a difference between the origins of death in our cases. Methods: Tattoos found in cases of natural death and suicide who underwent autopsy between 01/01/2020 and 31/07/2022 in Denizli, were evaluated retrospectively. Analysis was performed using the parameters of number, location, and type of tattoos. This study included 19 natural deaths and 35 suicides. There were 29 (82.9%) male, 6 (17.1%) females who committed suicide. In the natural deaths, there were 16 (84.2%) male, 3 (15.8%) were female. The mean age of suicide cases was 30.34±9.47, natural deaths was 43.84±10.7. Results: We did not find a significant difference in the number, type, and location of tattoos between suicides and natural deaths. The mean number of tattoos was higher in suicides than in natural deaths, but there was no statistically significant difference in the total number of tattoos between the two groups (p=0.647). Suicides tended to have a higher mean number of shape/geometric/illustrative tattoos, and animal/creature tattoos, compared to natural deaths. Conclusion: In our study, the tattoos were described in detail, analyzed according to the origin of death, and contributed to the literature on tattoo figures.